PEMANFAATAN PODCAST NOICE SEBAGAI MEDIA INFORMASI DAN MEDIA HIBURAN BAGI MAHASISWA: Studi Kasus Mahasiswa Pengguna “Noice” di Kota Surakarta - Nur Rahman, Arief Rizki; Kusumo Aji, Haryo; Muadz, Muadz (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This study discusses the use of Noice podcasts as a medium of information and entertainment for students in Surakarta City. Podcasts are increasingly in demand by the public, especially students, because of their flexibility in presenting various types of content that can be accessed anytime and anywhere. The formulation of the problem in this study is how to use Noice podcasts as a medium of information and entertainment for students? Using qualitative descriptive methods, data collection was carried out through interviews, observations, and documentation of students who actively listen to Noice podcasts. The results of the study show that Noice podcasts are effective in conveying information and providing relevant and useful entertainment. A variety of content and features such as video podcasts, live streaming, and downloads provide convenience and flexibility for listeners. This study concludes that Noice podcasts have a positive impact on increasing insight and as a means of relieving stress for students. It is recommended for Noice developers to continue to improve the quality of content and services in order to improve the user experience.